Integration of Google Sites in Merdeka Curriculum: Differentiated Learning Solutions in Elementary School - Fitriyah, Fitriyah; Turmudzi, Imam (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
Integrating technology into classrooms is essential in the digital transformation era to support diverse learning needs and foster inclusive education. Differentiated learning has emerged as a key pedagogical approach to address student diversity by tailoring instruction based on individual abilities, interests, and learning paces. This study examines the dominance of conventional teaching methods at SD 24 Dauh Puri Denpasar and explores the potential of Google Sites in supporting differentiated learning through a qualitative research approach. Data were collected using classroom observations, surveys, and focus group discussions (FGDs) to understand both teachers' instructional practices and students' learning preferences. However, there is a noticeable lack of studies that specifically examine the use of Google Sites within the context of the Merdeka Curriculum, highlighting the need for further research on how this platform supports differentiated instruction aligned with the curriculum’s principle. Findings reveal that 65% of teachers predominantly use lecture-based instruction due to limited technological resources, despite 70% of students preferring technology-based learning for its interactive and engaging nature. Google Sites has proven effective in catering to diverse learning needs by offering customized instructional materials, interactive exercises, and self-paced learning opportunities. However, challenges such as limited access to digital devices, unstable internet connectivity, and teachers' lack of technological proficiency hinder its full implementation. The study highlights the need for schools to enhance digital infrastructure, provide continuous teacher training, and develop policies that support technology integration. These findings align with the Merdeka Curriculum, emphasizing flexible, student-centered learning approaches. While Google Sites presents a promising solution for differentiated instruction, further research is needed to address accessibility issues and evaluate its long-term impact on student learning outcomes. The findings offer guidance for schools implementing flexible, technology-supported instruction within the Merdeka Curriculum.